Website Design for Ordering and Management of Traditional Food Stalls with A Responsive Display - Denisa Kartinah; Roni Ilham Subagja; Komarudin Komarudin; Isak Ramlan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the foundation of Indonesia's economy, especially in the traditional culinary sector. A family restaurant, in operation since 2013, struggles to manage operations because its manual recording system relies on notebooks and basic records. This problem results in a significant frequency of order inaccuracies (3-6 occurrences daily), an average wait time of around 22 minutes, and challenges in inventory oversight. This project seeks to develop a cohesive, user-friendly ordering and administration website, with a responsive design, to address these operational issues. The study used a qualitative methodology, encompassing four months of observation, interviews with the restaurant proprietor, and literature reviews. The system development employs the Laravel Framework within an object-oriented programming paradigm, while requirements analysis is performed using use case, class, and sequence diagrams. The results demonstrate that implementing the ordering website substantially enhances the restaurant's operational efficiency. The system effectively substitutes the traditional ordering process, minimizes recording errors, accelerates service, and offers clients the ease of online ordering without temporal or locational constraints. The real-time inventory management tool enables the owner to precisely track stock levels, while the automatic transaction recording system improves the accuracy of financial reports. This study illustrates that digital transformation via an ordering website can preserve the attributes of a traditional warung while enhancing service quality and fostering the growth of culinary MSMEs in Indonesia.